Viral and Nonviral Engineering of Natural Killer Cells as Emerging Adoptive Cancer Immunotherapies - Sandro Matosevic (Journal of Immunology Research)
Natural killer (NK) cells are powerful immune effectors whose antitumor activity is regulated through a sophisticated network of activating and inhibitory receptors. As effectors of cancer immunotherapy, NK cells are attractive as they do not attack healthy self-tissues nor do they induce T cell-driven inflammatory cytokine storm, enabling their use as allogeneic adoptive cellular therapies. Clinical responses to adoptive NK-based immunotherapy have been thwarted, however, by the profound immunosuppression induced by the tumor microenvironment, particularly severe in the context of solid tumors. In addition, the short postinfusion persistence of NK cells in vivo has limited their clinical efficacy. Enhancing the antitumor immunity of NK cells through genetic engineering has been fueled by the promise that impaired cytotoxic functionality can be restored or augmented with the use of synthetic genetic approaches. Alongside expressing chimeric antigen receptors to overcome immune escape by cancer cells, enhance their recognition, and mediate their killing, NK cells have been genetically modified to enhance their persistence in vivo by the expression of cytokines such as IL-15, avoid functional and metabolic tumor microenvironment suppression, or improve their homing ability, enabling enhanced targeting of solid tumors. However, NK cells are notoriously adverse to endogenous gene uptake, resulting in low gene uptake and transgene expression with many vector systems. Though viral vectors have achieved the highest gene transfer efficiencies with NK cells, nonviral vectors and gene transfer approaches—electroporation, lipofection, nanoparticles, and trogocytosis—are emerging. And while the use of NK cell lines has achieved improved gene transfer efficiencies particularly with viral vectors, challenges with primary NK cells remain. Here, we discuss the genetic engineering of NK cells as they relate to NK immunobiology within the context of cancer immunotherapy, highlighting the most recent breakthroughs in viral vectors and nonviral approaches aimed at genetic reprogramming of NK cells for improved adoptive immunotherapy of cancer, and, finally, address their clinical status.